Transparency in Business An Integrative View - Dholakia, Utpal (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This ambitious book develops an integrative understanding of business transparency spanning business disciplines. It synthesizes the vast, siloed research on business transparency to develop and provide an integrative view for business researchers and scholars, pointing out research opportunities in the process. The first chapter introduces business transparency with a brief historical overview, followed by its key conceptualizations and challenges. Chapters 2 through 5 take up four conceptually distinct views of transparency in depth: transparency as strategic disclosure (Chapter 2), transparency as a business tactic (Chapter 3), transparency as organizational culture (Chapter 4) and transparency as a managerial virtue (Chapter 5). Chapter 6 explores transparency's infeasibility challenge through the chasm between disclosure and understanding and considers its implications. The final chapter provides an integrative framework of business transparency. This book will be useful to business academics who are interested in transparency and associated concepts. Utpal Dholakia is a Professor of Marketing and holds the George R. Brown chair at the Jones Graduate School of Business, Rice University, USA. He has published over a hundred articles and written two books. His academic work concerns pricing strategy, customer experience, entrepreneurship, and digital marketing.
Chapter 1. The Many Shades of Business Transparency -- Chapter 2. Transparency as a Managerial Virtue -- Chapter 3. Transparency as Tactical Observability -- Chapter 4. Transparency as Information Disclosure -- Chapter 5. Transparency as Organizational Culture -- Chapter 6. The Benefits of Transparency -- Chapter 7. The Drawbacks of Transparency -- Chapter 8. Bringing it all together: An Integrated Framework of Business Transparency. .
Keywords: Management; Industrial organization; Strategic planning; Leadership; Marketing; Production management; Management; Organization; Business Strategy and Leadership; Marketing; Operations Management